THE EXTENT OF PRAGMALINGUISTICS ACQUISITION IN ENGLISH AND UZBEK LINGUISTICS - Anora Abduraimova (Bright Mind Publishing, 2025)
This study explores the level of pragmalinguistic competence in English and Uzbek linguistic studies, focusing on how each language's scholars and learners acquire and apply pragmatic language use. Pragmalinguistics, a subfield of pragmatics, studies the linguistic resources that speakers use to perform communicative acts. The paper uses qualitative content analysis of textbooks, academic curricula, and learner performance to assess the extent of pragmalinguistics integration in both English and Uzbek linguistics. Findings reveal significant differences in depth and focus, suggesting broader implications for curriculum development and language instruction in multilingual contexts.